Separator substrate for fuel cell

CN122930944APending Publication Date: 2026-10-16TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610330737.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-09
Filing Date
2026-03-18
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0006] In the second approach, in the first approach described above, the F/Fe ratio in the passivation film can be 0.01 or higher. Here, F represents fluorine, and Fe represents iron. Furthermore, both the amount of F and the amount of Fe are at% (atomic percentage). F represents the charge carriers of electrons. Therefore, by making the F/Fe ratio in the passivation film 0.01 or higher, the contact resistance of the passivation film can be sufficiently reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930944A_ABST
    Figure CN122930944A_ABST
Patent Text Reader

Abstract

The separator substrate for fuel cells of the present invention is composed of a stainless steel material having a passivation film. A plurality of pits are formed on the surface of the passivation film. The arithmetic average roughness of the surface is 6 nm or more and 18 nm or less. The average depth of the pits is 20 nm or more and 100 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technology disclosed in this specification relates to a separator substrate for fuel cells. Background Technology

[0002] Japanese Patent No. 5,109,234 discloses a separator substrate for fuel cells. This separator substrate is made of stainless steel with a passivation film. Regarding the passivation film, it is described that the average interval between local peaks on its surface roughness curve is 0.3 μm or less. Summary of the Invention

[0003] As with the aforementioned insulating substrate, in an insulating substrate made of stainless steel, the contact resistance of the insulating substrate can be reduced by modifying the passivation film. This specification also provides a new technique for reducing the contact resistance of an insulating substrate by modifying the passivation film.

[0004] The technology disclosed in this specification is specifically embodied in a separator substrate for fuel cells. In a first embodiment, the separator substrate is made of stainless steel material having a passivation film. Multiple pits are formed on the surface of the passivation film. The arithmetic mean roughness (Ra) of the surface is 6 nm or more and 18 nm or less. The average depth of the pits is 20 nm or more and 100 nm or less.

[0005] The inventors of this invention discovered that if the surface of the passivation film has multiple pits, the contact resistance of the separator substrate is significantly reduced. Furthermore, based on this insight, they conducted repeated and in-depth research and found that when the arithmetic mean roughness (Ra) of the surface and the average depth of the pits are within the aforementioned ranges, the contact resistance is sufficiently reduced. By using this separator substrate in a fuel cell, the power generation efficiency of the fuel cell can be improved.

[0006] In the second approach, in the first approach described above, the F / Fe ratio in the passivation film can be 0.01 or higher. Here, F represents fluorine, and Fe represents iron. Furthermore, both the amount of F and the amount of Fe are at% (atomic percentage). F represents the charge carriers of electrons. Therefore, by making the F / Fe ratio in the passivation film 0.01 or higher, the contact resistance of the passivation film can be sufficiently reduced. Attached Figure Description

[0007] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention are described below with reference to the accompanying drawings, wherein like symbols denote like elements, wherein:

[0008] Figure 1 This is a diagram that briefly illustrates the structure of the isolation member substrate 10 in the embodiment.

[0009] Figure 2AThis is an example of a SEM image of the surface of the insulating substrate of an embodiment.

[0010] Figure 2B This is an example of a SEM image of the surface of a comparative example of a spacer substrate.

[0011] Figure 3A This is an example of a TEM image of a cross-section of the insulating substrate of an embodiment.

[0012] Figure 3B This is an example of a TEM image of a cross-section of a comparative example spacer substrate.

[0013] Figure 4A This is a graph showing the relationship between the average depth of the pit and the F / Fe ratio.

[0014] Figure 4B This is a graph showing the relationship between the arithmetic mean roughness (Ra) of a surface and the F / Fe ratio. Detailed Implementation

[0015] Referring to the accompanying drawings, the separator substrate 10 of this embodiment will be described. The separator substrate 10 of this embodiment has a plate shape. Separators for fuel cells can be manufactured by forming through holes and / or grooves, etc., on the separator substrate 10 of this embodiment. The separator substrate 10 is made of stainless steel. Examples of stainless steel materials include austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, and austenitic-ferritic (duplex) stainless steel. Specific examples of stainless steel materials include SUS301, SUS304, SUS316, SUS430, SUS430J1L, SUS434, SUS444, and SUS631. The thickness of the separator substrate 10 is not particularly limited, but is, for example, 0.05 mm or more and 0.3 mm or less.

[0016] like Figure 1 As shown, the isolation component substrate 10 includes a substrate body 12 and a passivation film 14. The passivation film 14 is disposed on the surface of the substrate body 12 (here, the surface in the +Y direction). The thickness of the passivation film 14 is not particularly limited, for example, it is 0.1 nm or more and 20 nm or less.

[0017] like Figure 1 As shown, the passivation film 14 has a plurality of pits 16. Each of the plurality of pits 16 is a depression with a generally circular opening. The opening diameter of each pit 16 is not particularly limited, for example, it is 25 nm or more and 200 nm or less. The plurality of pits 16 are formed on the surface of the passivation film 14 (here, the plane in the +Y direction). The plurality of pits 16 are irregularly distributed on the surface of the passivation film 14. The portion of the surface of the passivation film 14 in which no pits 16 are formed is a generally flat surface.

[0018] The multiple pits 16 have different depths. The depth referred to here is the distance from the surface of the passivation film 14 to the deepest point of the pit 16. The average depth of the multiple pits 16 is, for example, 20 nm or more and 100 nm or less, or, for example, 25 nm or more and 90 nm or less, or, for example, 30 nm or more and 80 nm or less. The average depth of the multiple pits 16 is calculated, for example, as the average of values ​​obtained by measuring the depth of the multiple pits 16 in a cross-section observed by a transmission electron microscope (TEM). However, the multiple pits 16 may also have the same depth.

[0019] The arithmetic mean roughness (Ra) of the surface of the passivation film 14 is, for example, 6 nm or more and 18 nm or less, or, for example, 10 nm or more and 16 nm or less. Here, the arithmetic mean roughness (Ra) is specified by JIS B0601:2013. The arithmetic mean roughness (Ra) can be calculated, for example, based on a surface roughness profile measured using an atomic force microscope (AFM).

[0020] The F / Fe ratio in the passivation film 14 is not particularly limited, but may be, for example, 0.01 or more, 0.02 or more, or 0.05 or more. The F / Fe ratio in the passivation film 14 is calculated, for example, based on the amount of F and Fe in the passivation film 14 as determined by surface X-ray photoelectron spectroscopy (XPS). The amount of F in the passivation film 14 is, for example, 0.5 at% or more and 5.0 at% or less, and the amount of Fe in the passivation film 14 is, for example, 5.0 at% or more and 15.0 at% or less.

[0021] The inventors of this invention discovered that if the surface of the passivation film 14 has multiple pits 16, the contact resistance of the separator substrate 10 is significantly reduced. Furthermore, based on this insight, they conducted repeated and in-depth studies and found that, as in the embodiment described above, when the arithmetic mean roughness (Ra) of the surface is 6 nm or more and 18 nm or less, and the average depth of the pits is 20 nm or more and 100 nm or less, the contact resistance is sufficiently reduced. By using this separator substrate 10 in a fuel cell, the power generation efficiency of the fuel cell can be improved.

[0022] Furthermore, although this is just one example, the F / Fe ratio in the passivation film 14 is 0.01 or higher. F represents the charge carrier of electrons. Therefore, by making the F / Fe ratio in the passivation film 14 0.01 or higher, the contact resistance of the passivation film 14 can be sufficiently reduced.

[0023] Next, the manufacturing method of the separator substrate 10 according to the embodiment will be described. In this manufacturing method, the passivation film 14 of the stainless steel material having a plate shape is modified.

[0024] The manufacturing method includes a first step of heat-treating the insulating substrate 10. In this first step, the heat treatment is performed in the atmosphere or in an inert gas atmosphere such as nitrogen or Ar. The temperature at this time is, for example, 100°C or higher and 700°C or lower. The heat treatment time is, for example, 30 seconds or more and 30 minutes or less.

[0025] The manufacturing method further includes a second step of injecting fluorine into the passivation film 14. In the second step, the stainless steel material, which has undergone heat treatment in the first step, is subjected to pulse electrolysis in an aqueous solution containing fluoride ions. Thus, an anodic potential and a cathode potential are alternately applied to the stainless steel material. The anodic current density is, for example, 0.05 A / dm³. 2 Above and 1.0A / dm 2 The cathode current density is, for example, 0.05 A / dm³. 2 Above and 5.0A / dm 2 The pulse electrolysis time is, for example, 10 seconds or more but less than 10 minutes. Here, the pulse electrolysis time is the total time of the anode pulse time and the cathode pulse time. The anode pulse time is the time during which the anode potential is applied, and the cathode pulse time is the time during which the cathode potential is applied. The anode pulse time and the cathode pulse time can each be varied arbitrarily within the range of the pulse electrolysis time. It should be noted that in pulse electrolysis, the initially applied potential can be either the anode potential or the cathode potential.

[0026] As a fluoride ion source for fluorine injection, there are no limitations on the use of hydrofluoric acid or fluorine compounds that dissolve in water to generate fluoride ions; any compound can be used. Examples of fluoride ion sources include alkali metal fluorides such as sodium fluoride and potassium fluoride, ammonium fluoride, antimony trifluoride, copper fluoride, sodium difluoride, and potassium difluoride. The pH of the aqueous solution containing fluoride ions is, for example, above 0 and below 3. The concentration of fluoride ions in the aqueous solution is, for example, 0.001 kmol / m³. 3 The concentration must be above the saturation level and below the saturation level. For example, the temperature of an aqueous solution containing fluoride ions must be above 10°C and below 30°C.

[0027] The manufacturing method further includes a third step of modifying the passivation film 14 in an alkaline aqueous solution or a non-aqueous solvent. In this third step, the stainless steel material that underwent pulse electrolysis in the second step is subjected to pulse electrolysis in an alkaline aqueous solution or a non-aqueous solvent. This involves alternately applying anodic and cathodic potentials to the stainless steel material. The anodic current density and the cathodic current density are each, for example, 0.001 A / dm³.2 Above and 10A / dm 2 The pulse electrolysis time is, for example, 5 seconds or more and 10 minutes or less. The anode pulse time and cathode pulse time can each be varied arbitrarily within the range of the pulse electrolysis time. It should be noted that in pulse electrolysis, the initially applied potential can be either the anode potential or the cathode potential. However, in the third process, anodic electrolysis with only the anode potential applied can be used instead of pulse electrolysis.

[0028] Examples of alkaline aqueous solutions include sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, magnesium hydroxide solution, barium hydroxide solution, lithium hydroxide solution, and ammonium hydroxide solution. Examples of non-aqueous solvents include ethanol, methanol, dimethyl ether, diethyl ether, and methyl ethyl ether. Alternatively, a mixture of water and a water-mixable non-aqueous solvent can be used. The pH of the alkaline aqueous solution is, for example, 10 or higher. The temperature of the alkaline aqueous solution or the non-aqueous solvent is 10°C or higher and 30°C or lower.

[0029] The manufacturing method further includes a fourth step of dissolving iron from the passivation film 14. In this fourth step, the stainless steel material, which underwent pulse electrolysis in the third step, is immersed in an aqueous solution containing fluoride ions. Examples of the aqueous solution containing fluoride ions include hydrofluoric acid, or an acidic aqueous solution obtained by adding acid to the aforementioned fluoride ion source. The pH of the aqueous solution containing fluoride ions is, for example, 0 or higher and 3 or lower. The concentration of fluoride in the aqueous solution is, for example, 0.001 kmol / m³. 3 The concentration is above and below the saturation concentration. Examples of acids used for pH adjustment include nitric acid, sulfuric acid, and phosphoric acid. For example, the concentration of an acid used for pH adjustment in aqueous solution is 0.01 kmol / m³. 3 Above and 10 kmol / m 3 The following applies: The temperature of the aqueous solution containing fluoride ions is, for example, above 10°C and below 80°C. The immersion time is, for example, above 5 seconds and above 20 minutes.

[0030] According to the manufacturing method described above, a plurality of pits 16 having an average depth of 20 nm or more and 100 nm or less can be formed on the passivation film 14 of stainless steel material. Furthermore, due to these pits 16, the arithmetic mean roughness (Ra) of the surface of the passivation film 14 is 6 nm or more and 18 nm or less. Therefore, the isolation component substrate 10 of this embodiment can be manufactured using the manufacturing method described above.

[0031] The following describes embodiments related to this technology, but it is not intended to limit this technology to the content shown in the embodiments.

[0032] (Example 1)

[0033] In Example 1, as shown in Table 1, firstly, as a first step, SUS304 stainless steel material (plate thickness: 0.2 mm) was heated at 550°C for 1 minute in atmospheric air. Secondly, the heated stainless steel material was subjected to 60-second pulse electrolysis in a 5% (w / w) HF aqueous solution. At this time, both the anolyte current density and the cathode current density were 0.36 A / dm³. 2 As the third step, the SUS304 is processed at 1 kmol / m 3 A 10-second pulse electrolysis was further performed in an aqueous LiOH solution. During this time, both the anolyte current density and the cathode current density were 1.0 A / dm³. 2 Finally, as the fourth step, the SUS304 was immersed in a 5% by mass HF aqueous solution for 10 seconds to produce the insulating substrate 10 of Example 1.

[0034] [Table 1]

[0035]

[0036] (Example 2)

[0037] As shown in Table 1, in Example 2, instead of Example 1, a 10-second pulse electrolysis was performed using an aqueous LiOH solution at a concentration of 1 kmol / m 3 Anodizing was performed for 5 seconds in an aqueous LiOH solution. Except for this point, Example 2 was the same as Example 1.

[0038] (Example 3)

[0039] As shown in Table 1, in Example 3, the cathode current density in the pulse electrolysis using HF aqueous solution in Example 1 was changed to 3.0 A / dm³. 2 In addition, the pulse electrolysis time using LiOH aqueous solution in Example 1 was changed to 60 seconds. Furthermore, instead of heating at 550°C for 1 minute and then at 500°C for 5 minutes as in Example 1, Example 3 was identical to Example 1.

[0040] (Example 4)

[0041] As shown in Table 1, in Example 4, compared with Example 3, the anode current density and cathode current density in the pulse electrolysis using LiOH aqueous solution were changed to 3.0 A / dm³. 2 Except for this point, Example 4 is the same as Example 3.

[0042] (Example 5)

[0043] As shown in Table 1, in Example 5, compared with Example 3, the anode current density and cathode current density in the pulse electrolysis using LiOH aqueous solution were changed to 0.01 A / dm³. 2 Except for this point, Example 5 is the same as Example 3.

[0044] (Comparative Example 1)

[0045] As shown in Table 1, in Comparative Example 1, the anode current density and cathode current density in the pulse electrolysis using HF aqueous solution in Example 1 were changed to 0.004 A / dm³. 2 Additionally, the pulse electrolysis time using LiOH aqueous solution in Example 1 was changed to 20 seconds. Apart from these points, Comparative Example 1 was identical to Example 1.

[0046] (Comparative Example 2)

[0047] As shown in Table 1, in Comparative Example 2, the pulse electrolysis time of the HF aqueous solution used in Comparative Example 1 was changed to 20 seconds. Except for these points, Comparative Example 2 is the same as Comparative Example 1.

[0048] (Comparative Example 3)

[0049] As shown in Table 1, in Comparative Example 3, the anolyte current density in the pulse electrolysis using an aqueous HF solution in Example 3 was changed to 0.18 A / dm³. 2 Apart from this, Comparative Example 3 is the same as Example 3.

[0050] (Comparative Example 4)

[0051] As shown in Table 1, Comparative Example 4 used SUS304 as the stainless steel material. That is, Comparative Example 4 was SUS304 without any treatment.

[0052] (Arithmetic mean roughness)

[0053] Using atomic force microscopy, the arithmetic mean roughness (Ra) of the passivation film surface of the spacer substrate in each example was measured under the conditions shown below. The surface of the passivation film of the spacer substrate in each example was scanned at three different locations along the longitudinal direction (i.e., the Z-direction), resulting in three surface roughness curves. Similarly, the surface was scanned at three different locations along the transverse direction (i.e., the X-direction), resulting in three surface roughness curves. After flattening these six surface roughness curves using Flatten and PlaneFit filters, the average surface roughness over the scanned distance was calculated, and this average value was taken as the arithmetic mean roughness (Ra). The results are shown in Table 2.

[0054] Device Name: Bruker Dimension Icon

[0055] • Measurement conditions: tapping mode

[0056] • Scan speed: 0.8Hz

[0057] • Measurement points: 512×512 points

[0058] (Average depth of the pit)

[0059] The surfaces of the spacer substrates in each example were pretreated using a focused ion beam (FIB) device. The surfaces of the spacer substrates in each example were observed using a scanning transmission electron microscope (STEM) under the conditions shown below in five different fields of view (see reference). Figure 2A , Figure 2B In each field of view, the substrate of the spacer is cut along the thickness direction at any position, and the cross-section is observed using TEM (refer to...). Figure 3A , Figure 3B The depths of multiple pits in the TEM images of each cross section were measured, and their average value was calculated as the average depth of the pits. The results are shown in Table 2.

[0060] • Device Name: Hitachi High-Tech HD-2700

[0061] Accelerating voltage: 200kV

[0062] • Viewing mode: ZC image

[0063] Multiplier: 50,000x

[0064] (F / Fe ratio)

[0065] The amounts of F (at%) and Fe (at%) in the passivation film of the separator substrates in each example were measured under the conditions shown below, and the F / Fe ratio in the passivation film was calculated. The results are shown in Table 2.

[0066] • Device: ULVAC-PHI PHI5000 Versa Probe II

[0067] • Analysis area: 200×1400μm

[0068] • X-ray source: Monochromatic AlKα (1486.6 eV)

[0069] • Photoelectron emission angle: 90° (sample normal direction)

[0070] • Charge correction: C1s 285eV (hydrogen hydrocarbons)

[0071] (Contact resistance)

[0072] The substrate of each insulating element was cut into 15mm × 50mm pieces to prepare test samples. The initial and durable contact resistance of each test sample was measured under the conditions shown below. The initial contact resistance refers to the contact resistance measured for the first time after preparation of the test sample. The durable contact resistance refers to the contact resistance measured after immersing the prepared test sample in an FCC solution (ethylene glycol:water = 50:50) and placing it at 85°C for 1000 hours. The results are shown in Table 2.

[0073] • Device: Electrical contact simulator (CRS-113-mold) manufactured by Yamazaki Seiki Research Institute Co., Ltd.

[0074] • Measurement probe: PU-05 gold wire contact, 0.5mm Φ

[0075] • Apply constant current: 10mA

[0076] [Table 2]

[0077]

[0078] According to the results shown in Table 2, in the insulating substrate, when the arithmetic mean roughness (Ra) of the passivation film surface is 6 nm or more and 18 nm or less, and the average depth of the pits formed on the surface is 20 nm or more and 100 nm or less, the initial and durable contact resistance is sufficiently reduced.

[0079] In addition, as shown in Table 2 and Figure 4A As shown in Figure 4B, when the F / Fe ratio in the passivation film is above 0.01, the initial and durable contact resistance is significantly reduced. This is attributed to the presence of a higher concentration of F, which acts as an electron carrier, in the passivation film.

[0080] The manufacturing method described above may also omit the first step. Furthermore, in the manufacturing method described above, the third step may be performed before the second step. Alternatively, the second and third steps may be performed repeatedly in the manufacturing method described above.

[0081] The above provides detailed descriptions of specific examples, but these are merely illustrative and do not limit the scope of the patent claim. The technology described in the scope of the patent claim includes technologies obtained by various modifications and alterations to the specific examples illustrated above. The technical elements described in this specification or drawings may exert their technical usefulness individually or in combination.

Claims

1. A separator substrate, which is a separator substrate used in fuel cells. It is made of stainless steel with a passivation film. Multiple pits are formed on the surface of the passivation film. The arithmetic mean roughness of the surface is greater than 6 nm and less than 18 nm. The average depth of the pit is above 20 nm and below 100 nm.

2. The insulating substrate according to claim 1, wherein, The F / Fe ratio in the passivation film is 0.01 or higher.

Citation Information

Patent Citations

  • Batsuteriodengentosuru inbaatakairo

    JP1976009234A